Are white-lipped peccaries from Argentinean Yungas looking to a promising future? - Reppucci, Juan I. (2022)
The white-lipped peccary (Tayassu pecari) is considered a key species for its role as an ecosystem engineer. Given their important ecological function, there is a great concern in the scientific community regarding the many reports of disappearances or great abundance reductions throughout its distribution (from southern Mexico to northern Argentina). Based on an extensive survey effort, we report new data of presence of WLP after a period of no detections in the Argentine Yungas. The study was conducted in the Yungas ecoregion, provinces of Jujuy and Salta, Argentina. Data was collected from camera trap, direct sightings and footprints during 2013–2021. From a total of 30,186 trap nights, we obtained 8 WLP detections. There were no detections before 2017, while as of 2018 there was at least one camera trap record in each of the years. Additionally, opportunistic records were obtained yearly from 2019 to 2021. The period without detections could be related to a period of a population cycle, as suggested in different regions of America during the last century, being disease the most likely cause. These cycles generally follow a pattern of a rapid population decline, a period of absence or low abundance followed by slow population growth. We believe that if the trend continues and the number of detections increases, we could be facing the early stages of the increase phase in the WLP population cycle in the Argentine Yungas.